Faktor Risiko Personal dan Lingkungan dalam Kejadian Demam Tifoid - Kurniawan, Diva Ardhana; Apriliana, Ety; Sutarto, Sutarto; Himayani, Rani (Medula, 2024)
Typhoid fever is one of the infectious diseases that has a fairly high morbidity and mortality rate, especially in developing countries, especially in Indonesia. Typhoid fever is an infectious disease caused by the bacteria Salmonella typhi. This disease can be transmitted through consuming water or food contaminated with urine and feces from typhoid fever sufferers, for example, water that will be used for drinking, cooking, or washing food ingredients. There are more serious clinical symptoms, such as high fever or hyperthermia, remittent fever, and decreased level of consciousness that can lead to coma or delirium. Further complications such as dehydration and acidosis can also occur, which have negative impacts in cases of typhoid fever. The purpose of this review article is to determine what personal and environmental risk factors are present in the occurrence of typhoid fever. The method used in this study is a review article with specific research of various articles found, then combined and a summary conclusion is drawn. The journals used have been published for the past 5 years (2019-2024). The results and conclusions show that several personal and environmental risk factors in the occurrence of typhoid fever include age, gender, personal hygiene, and clean water sources.